KURIKULUM PENDIDIKAN ISLAM ANAK USIA DINI - Yusnani Batu Bara; Lydia Sartika (Jurnal Al Athfaal, 2023)
The education curriculum includes all activities in the learning environment that students will carry out under the guidance of education institutions , both in the clssroom and outside the classroom . curriculum is a very important thing inthe world of early childhood education , because reading and writing are the most important parts for realizing human development and progress. This is also reflected in the Al-Qur’an Surah Al- Alaq verse 1 which means read. The Islamic education curriculum in kindergarten is a series of educational activities in a fun way . The development of the curriculum in preschool is the activity of learning while playing , which can enrich children’s experiences in various ways, such as answering all questions from students , playing with nature, and so on .